Food Insecurity in Selected African Countries: Effect of Food Imports among Other Predictors - Oke, David Mautin; Bokana, Koye Gerry; Uddin, Godwin Enaholo (SPOUDAI Journal of Economics and Business, 2017)
It has been envisaged that Sub-Saharan Africa would remain the region with the highest level of food insecurity over the 2015-2025 period. This study, therefore, further investigates food insecurity and food imports in some selected African countries. The regression results based on the fixed effects model show that food imports, employment in Agriculture, and food production have helped to reduce food insecurity in the five biggest African economies. However, livestock production, crop production, cereal yield as well as agricultural land area have not been able to reduce food insecurity in these countries. Agriculture value added per worker/food insecurity nexus was insignificant. Although, food importation remains a strong option for African countries in reducing their levels of food insecurity, policy measures by each country should be conceptualized based on their food security historical paths, environmental concerns, as well as their political, social and economic health. JEL Classifications: C33, E49, Q18